Usefulness of combined NGS and QF‐PCR analysis for product of conception karyotyping. (27th February 2022) - Kato, Takema; Miyai, Shunsuke; Suzuki, Hideki; Murase, Yuuri; Ota, Shiyo; Yamauchi, Hiroko; Ammae, Michiko; Nakano, Tatsuya; Nakaoka, Yoshiharu; Inoue, Tomoko; Morimoto, Yoshiharu; Fukuda, Aisaku; et al.
Abstract: Purpose: Since chromosomal abnormalities can be detected in more than half of miscarriages, cytogenetic testing of the product of conception (POC) can provide important information when preparing for a subsequent pregnancy. Conventional karyotyping is the common diagnostic method for a POC but can be problematic due to the need for cell culture. Methods: We here conducted shallow whole‐genome sequencing (sWGS) using next‐generation sequencing (NGS) for alternative POC cytogenomic analysis. Since female euploidy samples can include 69, XXX triploidy, additional QF‐PCR was performed in these cases. Results: We here analyzed POC samples from miscarriages in 300 assisted reproductive technology (ART) pregnancies and detected chromosomal abnormalities in 201 instances (67.0%). Autosomal aneuploidy (151 cases, 50.3%) was the most frequent abnormality, consistent with prior conventional karyotyping data. Mosaic aneuploidy was detected in seven cases (2.0%). Notably, the frequency of triploidy was 2.3%, 10‐fold lower than the reported frequency in non‐ART pregnancies. Structural rearrangements were identified in nine samples (3%), but there was no case of segmental mosaicism. Conclusions: These data suggest that NGS‐based sWGS, with the aid of QF‐PCR, is a viable alternative karyotyping procedure that does not require cell culture. This method could also assist with genetic counseling for couples who undergoes embryo selection based on PGT‐A data. Abstract : sWGS by NGS combined with QF‐PCR is the optimal diagnostic method for cytogenetic testing of POC samples.